Hermeneutika Al-Qur'an dalam Perspektif Farid Essack - Munfarida, Elya (Al-Manahij: Jurnal Kajian Hukum Islam, 2008)
Reception hermeneutic toward Al-Qur'an in Farid Essack perspective is not only able to accommodate the history of texts but also to give space for readers to ˜have dialogues with text based on social contexts. This approach is applied as a to get objective interpretation especially in South Africa with its characteristic (rasism, economic exploitation, etc).